Characterization of Mg-containing hydroxyapatites synthesized by combustion method - Kaygili, Omer; Keser, Serhat; Bulut, Niyazi; Ates, Tankut (Elsevier, 2018)
In the present paper, Mg-substituted hydroxyapatites with the morphology, composed of the stacked plate-and rod-like structures, were prepared at the temperature of 600 degrees C by combustion method using glycerine as a fuel. A significant decrease in the crystallite size values calculated for both Scherrer and Williamson-Hall methods is found. The crystallinity, lattice parameter of a, stress and anisotropic energy density values decreased by adding of Mg, whereas the lattice strain increased. The amount of HAp phase decreases with increasing amount of Mg and the beta-tricalcium phosphate content increases. Mg incorporation the apatitic structure was detected. Depending on the increase in Mg content, Ca-deficiency was observed.
Keywords: HydroxyApatite; Combustion method; X-ray diffraction (XRD); Morphology